Corticofugal modulation of peripheral auditory responses - Terreros, Gonzalo; Delano, Paul H. (Frontiers in Systems Neuroscience, 2015)
The auditory efferent system originates in the auditory cortex and projects to the medial geniculate body, inferior colliculus, cochlear nucleus and superior olivary complex reaching the cochlea through olivocochlear fibers. This unique neuronal network is organized in several afferent-efferent feedback loops including: the (i) colliculo-thalamic-cortico-collicular, (ii) cortico-(collicular)-olivocochlear and (iii) cortico-(collicular)-cochlear nucleus pathways. Recent experiments demonstrate that blocking ongoing auditory-cortex activity with pharmacological and physical methods modulates the amplitude of cochlear potentials. In addition, auditory-cortex microstimulation independently modulates cochlear sensitivity and the strength of the olivocochlear reflex. In this mini-review, anatomical and physiological evidence supporting the presence of a functional efferent network from the auditory cortex to the cochlear receptor is presented. Special emphasis is given to the corticofugal effects on initial auditory processing, that is, on cochlear nucleus, auditory nerve and cochlear responses. A working model of three parallel pathways from the auditory cortex to the cochlea and auditory nerve is proposed.